Catalyst‐Free Decarbonylative Trifluoromethylthiolation Enabled by Electron Donor‐Acceptor Complex Photoactivation. Issue 14 (1st June 2021) - Lipp, Alexander; Badir, Shorouk O.; Dykstra, Ryan; Gutierrez, Osvaldo; Molander, Gary A.
Abstract: A catalyst‐ and additive‐free decarbonylative trifluoromethylthiolation of aldehyde feedstocks has been developed. This operationally simple, scalable, and open‐to‐air transformation is driven by the selective photoexcitation of electron donor‐acceptor (EDA) complexes, stemming from the association of 1, 4‐dihydropyridines (donor) with N ‐(trifluoromethylthio)phthalimide (acceptor), to trigger intermolecular single‐electron transfer events under ambient‐ and visible light‐promoted conditions. Extension to other electron acceptors enables the synthesis of thiocyanates and thioesters, as well as the difunctionalization of [1.1.1]propellane. The mechanistic intricacies of this photochemical paradigm are elucidated through a combination of experimental efforts and high‐level quantum mechanical calculations [dispersion‐corrected (U)DFT, DLPNO‐CCSD(T), and TD‐DFT]. This comprehensive study highlights the necessity for EDA complexation for efficient alkyl radical generation. Computation of subsequent ground state pathways reveals that SH 2 addition of the alkyl radical to the intermediate radical EDA complex is extremely exergonic and results in a charge transfer event from the dihydropyridine donor to the N ‐(trifluoromethylthio)phthalimide acceptor of the EDA complex. Experimental and computational results further suggest that product formation also occurs via SH 2 reaction of alkyl radicals with 1, 2‐bis(trifluoromethyl)disulfane, generated in‐situ through combination of thiyl radicals. Abstract :